ANALISIS KESALAHAN MAHASISWA DALAM MEMECAHKAN MASALAH TRIGONOMETRI - Sri Adi Widodo; A.A Sujadi (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2015)
The aim of this research to know the error of problem solving in trigonometry. This research used the qualitative descriptive, with the subject of research is 80 students who were taken be based on purposive sampling. The procedure of the data was used by the think out louds. Technically the analysis of the data that was used was (1) studied all the data’s that were gathered, (2) studied results of the work of the student in resolving the problem of trigonometry, (3) carried out the verification from the data. The checking of the legality of the data used the triangulation. The first and second stage of error was the concept, the third stage of error was the algorithm, and the fourth stage of error was habits and Confirmation of the answer. Keyword: error,  problem solving,  trigonometry